2023
DOI: 10.1002/jsfa.13087
|View full text |Cite
|
Sign up to set email alerts
|

Removal of ochratoxin A in wine by Cryptococcus albidus and safety assessment of degradation products

Leran Wang,
Rui Cai,
Jierong Zhang
et al.

Abstract: BACKGROUNDOchratoxin A (OTA) is a mycotoxin that contaminates grape‐based products and is extremely harmful to the health of the host. It is effectively removed by yeast during the fermentation of wine, whereas the removal mechanism of OTA remains unclear. Therefore, the present study aimed to investigate the removal mechanism of ochratoxin A by yeast and to evaluate the safety of its degradation products.RESULTSCryptococcus albidus (20‐G) with better effect on ochratoxin A (OTA) was screened out in the main f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Biological methods have many advantages, such as low cost and minimal side effects, and with the increasing awareness of environmental protection and food safety, they are the best representatives of the methods with lower environmental impact. They are widely used to reduce the concentration of OTA in food, grain, and feed [ 16 , 77 ]. Biological methods can be categorized into three groups based on the mechanisms of action: (1) inhibition of fungi responsible for OTA biosynthesis, (2) adsorption of OTA, and (3) degradation or detoxification of OTA in contaminated matrices [ 78 ].…”
Section: Biocontrol Of Ota Occurrence In Winementioning
confidence: 99%
See 1 more Smart Citation
“…Biological methods have many advantages, such as low cost and minimal side effects, and with the increasing awareness of environmental protection and food safety, they are the best representatives of the methods with lower environmental impact. They are widely used to reduce the concentration of OTA in food, grain, and feed [ 16 , 77 ]. Biological methods can be categorized into three groups based on the mechanisms of action: (1) inhibition of fungi responsible for OTA biosynthesis, (2) adsorption of OTA, and (3) degradation or detoxification of OTA in contaminated matrices [ 78 ].…”
Section: Biocontrol Of Ota Occurrence In Winementioning
confidence: 99%
“…As a result, a larger number of active sites are formed, which are responsible for the absorption of various compounds [ 116 ]. Although the results of several researchers have shown that LAB cells can adsorb OTA and it is removed or reduced from the medium in the absence of metabolically active cells, the results of other researchers have shown that metabolic degradation by hydrolysis of the amide bond or by hydrolysis of the lactone ring may be the mechanism responsible for OTA removal [ 77 , 84 , 88 , 89 , 91 , 114 ].…”
Section: Biocontrol Of Ota Occurrence In Winementioning
confidence: 99%